2007
DOI: 10.1080/14786410701371314
|View full text |Cite
|
Sign up to set email alerts
|

New synthesis of two tridentate bipyrazolic compounds and their cytotoxic activity tumor cell lines

Abstract: Two new tripodal compounds - 4-{bis[(3,5-dimethyl-1H-pyrazole-1-yl)methyl]amino}butane-1-ol (1); ethyl 1-[((2-hydroxyethyl){[3-(ethoxycarbonyl)-5-methyl-1H-pyrazole-1-yl]methyl} amino)methyl]-5-methyl-1H-pyrazole-3-carboxylate (2) were reported. The evaluation of the cytotoxic properties in vitro of these ligands, was examined on two tumor cell lines - P815 (mastocytome murine) and Hep (carcinoma of human larynx). The concentration required to induce 50% of lysis (IC(50)) was more pronounced against P815 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Then, the mixture was stirred at 65°C during 6 h. After filtration and evaporation to dryness, the obtained residue was purified through silica column using diethyl ether/ methanol 95:5 to give 6 as yellow oil (1.08 g, 67%). IR (7). To a mixture of 4 (1.5 g, 11.4 mmol) and anhydrous sodium carbonate (3.02 g, 28.5 mmol) in acetonitrile (30 ml), was added isopropane (0.34 g, 5.7 mmol) in acetonitrile (20 ml).…”
Section: Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the mixture was stirred at 65°C during 6 h. After filtration and evaporation to dryness, the obtained residue was purified through silica column using diethyl ether/ methanol 95:5 to give 6 as yellow oil (1.08 g, 67%). IR (7). To a mixture of 4 (1.5 g, 11.4 mmol) and anhydrous sodium carbonate (3.02 g, 28.5 mmol) in acetonitrile (30 ml), was added isopropane (0.34 g, 5.7 mmol) in acetonitrile (20 ml).…”
Section: Reagentsmentioning
confidence: 99%
“…In our laboratory, a number of pyrazole based tripodal ligands have been studied . These ligands incorporating in their structures two sp 2 and sp 3 hybridized amine nitrogen atoms, could be distinguish according to their side arms and the nature of junctions (N–C–N or N–C–C) that bound the pyrazole ring to the lateral arm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that the bridging carbon atom can be modified by the organic functional groups to form novel heteroscorpionate ligands 12 that are tailored toward different research applications like anticancer agents. [13][14][15] The coordination behaviour of these types of compounds can be easily adjusted by changing the electronic and steric characteristics of substituents on the 3-, 4-or 5-positions of the pyrazole ring. 12 Several pyrazole derivatives and their metal complexes have been reported in the literature [16][17][18][19] but very little attention has been paid to the atomic properties of the nitrogen donor atoms and their availability for metal coordination.…”
Section: Introductionmentioning
confidence: 99%